Capturing pre-service teachers’ development through service-learning - Abang Ahmad, Dayang Hartijah; Othman, Moomala; Jahedi, Maryam (International Institute for Science, Technology & Education, 2016)
This study aimed to investigate the effectiveness of a Community Service Learning (CSL) program in contributing to pre-service teachers' developmental growth. In this study, 20 TESL undergraduate students carried out a service-learning activity which involved a debate tournament program at a school where they taught and coached debate to 200 school students aged between 13 and 14 years old. With their assistance, these school students gained hands on experience debating. After the program, the pre-service teachers wrote their experience in their reflection log book. A survey was then undertaken to find out how much the program affected the trainee teachers both socially and academically. The analysis of their reflections indicated positive response of the program from everyone. Responses of pre-service teachers in the survey revealed that they have gained much personally, professionally and socially via CSL program. Likewise, the descriptive analysis of the survey provided insights into its benefits to students in general and ESL learners in particular.